2019
DOI: 10.3389/fchem.2019.00134
|View full text |Cite
|
Sign up to set email alerts
|

Task-Specific Organic Salts and Ionic Liquids Binary Mixtures: A Combination to Obtain 5-Hydroxymethylfurfural From Carbohydrates

Abstract: The increase in energy demand and depletion of fossil fuels are among major issues of modern society. Valorization and transformation of raw materials in products of industrial value represent a challenge. This justifies the growing interest of scientific research toward the identification of suitable media and methodologies able to pursue above goals, paying attention to matter of sustainability. On this subject, we studied sulfonic-acid functionalized diimidazolium salts as catalysts for the conversion of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 65 publications
(77 reference statements)
0
24
0
Order By: Relevance
“…Their high thermal stability, low vapor pressure and flammability favoured their application as solvents, 2 catalysts, 3 and reagents. 4 As more applications of ILs appear, there is also a growing attention to their biodegradability and toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Their high thermal stability, low vapor pressure and flammability favoured their application as solvents, 2 catalysts, 3 and reagents. 4 As more applications of ILs appear, there is also a growing attention to their biodegradability and toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The rate formation of HMF increases 40 times with Brønsted acidic ionic liquid, presumably because the good diffusion of Brønsted acidic ionic liquid into the reaction mixture enhances the dehydration reaction rate. D'Anna and coworkers reported the use of Amberlyst‐15 in [BMIM][BF 4 ] [31] or sulfonic‐acid functionalized diimidazoliumsalts [34] for the dehydration of fructose to produce HMF in high yield under conventional heating. Although the HMF was obtained in a lower yield than these reported methods, the fact that the reaction can reach completion within a short reaction time (only 45 s) makes the present method comparative regarding practicability to others in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31] Recently, it is also reported that ionic liquids can enhance the rate of formation of HMF from fructose. [22,[32][33][34] Additionally, ionic liquids have been shown to be effective in the synthesis of HMF using ionic liquid/organic solvent as a biphasic system. [35][36][37][38] Although interesting results could be obtained, the large-scale industrial feasibility of these approaches is limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, multi-charged ILs have been shown to have a greater range of physical properties than their monocationic counterparts, such as higher density, glass transition, melting point, surface tension, and shear viscosity [25]. Like traditional ILs, they can be task-specific ionic liquids depending on their chemical structures [26], [27], [28], [29], [30], [31], [32], [33], [34]. Notable recent examples include tetracationic acidic organic salt based on 1,4-diazabicyclo [2], [2], [2]octane (DABCO) that are used as catalyst in the Knoevenagel condensation reactions in water [29], [30].…”
Section: Introductionmentioning
confidence: 99%